Genotypic, phenothypic and environmental correlations in progenies of corn - Lemos, Margarida Agostinho; e Gama, Elto Eugenio Gomes; de Oliveira, Antônio Carlos; de Araújo, Marcelo Renato Alves (Pesquisa Agropecuaria Brasileira, 1992)
This paper presents estimates for genotypic, phenotypic and environmental correlation coefficients in the second cycle of selection for maize "Dentado composto" population, which envolved the following traits: plant height (PH), ear height (EH), ear number per plant (EN), ear number with husk problems (ENHP), Spodoptera frugiperda (SF), Heliothis zea (HZ) and grain yield (GY). Data came from experimental trials carried out at Empresa Pernambucana de Pesquisa Agropecuária (IPA) fields, in 1956. The genotypic correlations were greater than the phenotypic ones in all cases except for ENHP x HL The genotypic correlations were positive between GY and the PH and EN traits; between EH x HZ and between HZ x ENHP; negative between PH x SR, SF x HZ as well as between GY x SF and GY x HZ, indicating the importante of selection for resistance lo S. frugiperda and H. zea.